Kompleksowa fizjoterapia w astmie oskrzelowej - przegląd literatury = Comprehensive physical therapy in bronchial asthma - a literature review - Agnieszka Radzimińska; Sylwia Kozłowska; Katarzyna Strojek; Hanna Styczyńska; Walery Zukow (Kazimierz Wielki University, 2016)
Radzimińska Agnieszka, Kozłowska Sylwia, Strojek Katarzyna, Styczyńska Hanna, Zukow Walery. Kompleksowa fizjoterapia w astmie oskrzelowej - przegląd literatury = Comprehensive physical therapy in bronchial asthma - a literature review. Journal of Education, Health and Sport. 2016;6(10):53-67. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.159980 http://ojs.ukw.edu.pl/index.php/johs/article/view/3926         The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.09.2016. Revised 24.09.2016. Accepted: 08.10.2016.       Kompleksowa fizjoterapia w astmie oskrzelowej - przegląd literatury Comprehensive physical therapy in bronchial asthma - a literature review   Agnieszka Radzimińska¹, Sylwia Kozłowska¹, Katarzyna Strojek¹, Hanna Styczyńska¹, Walery Zukow2 1. Uniwersytet Mikołaja Kopernika w Toruniu Collegium Medicum w Bydgoszczy, Katedra Fizjoterapii, Zakład Podstaw Fizjoterapii, Bydgoszcz, Polska 2. WSG w Bydgoszczy, Bydgoszcz, Polska   Słowa kluczowe: fizjoterapia, astma oskrzelowa. Key words: physical therapy, bronchial asthma.       Streszczenie Astma oskrzelowa jest przewlekłą chorobą dróg oddechowych o charakterze zapalnym. Wyodrębnia się w niej okres międzynapadowy oraz okres, w którym występują nasilone objawy, takie jak: duszność, uporczywy kaszel, świszczący oddech, ból w klatce piersiowej oraz utrudniony wdech. Do podstawowych metod diagnostycznych zaliczamy badanie podmiotowe oraz badanie przedmiotowe, w których staramy się uzyskać jak najwięcej informacji od pacjenta. W celu potwierdzenia diagnozy dodatkowo wykonuje się testy skórne, badanie krwi, zdjęcie RTG oraz próby wysiłkowe. Podstawową metodą w programie rehabilitacji pulmonologicznej jest kinezyterapia. Zaliczamy do niej ćwiczenia ogólnousprawniające, ćwiczenia oddechowe ogólne oraz ćwiczenia wzmacniające siłę mięśni oddechowych. Bardzo ważnym elementem jest nauka efektywnego kaszlu, sprzyjająca ewakuacji wydzieliny z drzewa oskrzelowego. W momencie wystąpienia napadu dusznośći, oprócz natychmiastowego zastosowania leków interwencyjnych, pacjentowi nakazuje się przyjęcie odpowiedniej pozycji. Uzupełnieniem kompleksowego leczenia fizjoterapeutycznego jest masaż (klasyczny, segmentarny, drenaż), zabiegi z zakresu fizykoterapii, leczenie uzdrowiskowe oraz szerokopojęta edukacja pacjenta. Systematyczna oraz celowana rehabilitacja przynosi zadowalające efekty terapeutyczne, przyczyniając się do poprawy jakość życia chorych.     Abstract The bronchial asthma is a chronic respiratory disease of an inflammation. Isolated in it's the period between the attacks and the period in which you are experiencing severe symptoms, such as shortness of breath, persistent cough, wheezing, chest pain and difficult to breath. To the basic diagnostic methods include examination of symptoms and physical examination, where we try to get as much information as possible from the patient. In order to confirm the diagnosis in addition performs a skin test, blood test, radiograph and you try to stress. The basic method in the pulmonary rehabilitation is physiotherapy. Belonging to the exercise to improve general, breathing exercises and exercises to strengthen the overall strength of the respiratory muscles. A very important element is the science of effective cough, favoring the evacuation of secretions from the bronchial tree. At the time of the attack of breathlessness, in addition to immediate use drugs intervention, the patient requires the adoption of appropriate position. Complemented by comprehensive treatment is physiotherapy massage (classical, segmental, drainage), treatment with physiotherapy, spa treatment and patient education-reaching. The systematic and targeted rehabilitation brings satisfactory therapeutic effects, contributing to a better quality of life.